Exercise--it's never too late: the strong-for-life program. - Jette, A M (1999)
OBJECTIVES: This investigation determined whether an in-home resistance training program achieved health benefits in older adults with disabilities. METHODS: A randomized controlled trial compared the effects of assigning 215 older persons to either a home-based resistance exercise training group or a waiting list control group. Assessments were conducted at baseline and at 3 and 6 months following randomization. The program consisted of videotaped exercise routines performed with elastic bands of varying thickness. RESULTS: High rates of exercise adherence were achieved, with 89% of the recommended exercise sessions performed over 6 months. Relative to controls, subjects who participated in the program achieved statistically significant lower extremity strength improvements of 6% to 12%, a 20% improvement in tandem gait, and a 15% to 18% reduction in physical and overall disability at the 6-month follow-up. No adverse health effects were encountered. CONCLUSIONS: These findings provide important evidence that home-based resistance exercise programs designed for older persons with disabilities hold promise as an effective public health strategy.